MEMS-based semiconductor metal oxide gas sensors for harsh environment applications - Liu, Haotian (Nanyang Technological University, 2023)
Sulphur dioxide (SO2) is a critical substance in the corrosive sulfidation of aircraft engine blades. Monitoring the local SO2 concentrations in proximity to the engines requires the sensors to be able to operate in dry environment with high temperatures. However, the prevalent commercial sensors, based on the electrochemical principles, falter in such conditions due to the evaporation of the water in liquid electrolyte. This study advances the field of SO2 sensing through the development of novel conductometric MEMS gas sensors based on tungsten and vanadium oxides. Although semiconducting metal oxide gas sensors have been extensively studied in literature, SO2 attracts little attention due to its corrosive nature and a large variety of intermediate products generated in surface reaction. This study unravels the intricacies of surface science governing the interplay between metal oxides and SO2. The work commences with the exploration and optimization of the recipes for reactive sputtering of tungsten and vanadium oxide thin films. The development of microcracks on tungsten oxide films and extrusion of nanorods from vanadium oxide films indicates the fundamental difference in the grain movement mechanisms during thermal oxidation of these two types of metal oxides. The crack density and preferred orientation are found to be significantly affected by the deposition pressure and annealing conditions. Resistance measurement in different gas environments further reveals the surface adsorption mechanism and the route for charge transport from the thin film to the surface states. Crucially, the investigation uncovers intriguing behaviour in the resistance-temperature relationship, diverging from established semiconductor trends due to a phase transition from monoclinic to orthorhombic at 330°C. The research identifies the sensing temperature with highest response of 200 ◦C, maximizing response while noting a compelling phenomenon where the resistance only fully recovers above 350 ◦C. The study extends its innovation by exploring Microelectromechanical System (MEMS) technology for sensor miniaturization, enabling autonomous on-site applications. Finite Element Method (FEM) simulations guide the design of microheaters for uniform temperature distribution. The developed fabrication process results in microhotplates with embedded heater, enabling the sensor to reach 400 ◦C within 0.2 s. Local heating of the material on the membrane structure significantly reduces the total power consumption. Die attachment with nanocopper paste and encapsulation with Phthalonitrile guarantee the robustness of the sensors at over 300 ◦C. Remarkably, the integrated system showcases the ability to detect subtle changes in SO2 concentration as low as 0.2 ppm during sleep-operation switching mode, significantly surpassing existing commercial electrochemical-based sensors in terms of the baseline stability in dry environments. Furthermore, this research unearths the diverse transient response patterns in sensing behaviour towards other gases, including nitrogen dioxide, carbon monoxide, and water molecules. In conclusion, this research redefines SO2 gas sensing by rigorously develop conductometric sensors with tailored metal oxide thin films, innovative annealing techniques, and MEMS-enabled miniaturization. The resulting sensing system achieves supreme stability and adaptability, underscoring its potential for diverse industrial applications. Furthermore, the comprehensive workflow, encompassing material characterization, sensor design, microfabrication, packaging, and system integration, bestows invaluable insights into the system engineering of integrated gas monitoring systems.